Субъективная надежность: теория и метод измерения (ИСН) - Головаха, Е.; Горбачик, А.; Любивая, Т.; Панина, Н.; Середа, В.; Урсуленко, К. (Социология: теория, методы, маркетинг, 2008)
The paper provides a substantiation of the new procedure named ‘The Index of Sub jective Reliability’ (ISR). The authors examine various aspects concerning respondents’ self-estimation of their own reliability revealed in the responses to single questions, sets of questions and to the questionnaire as a whole. The results of question naire testing and evaluation in pilot and large-scale studies are also presented.